THE EFFECTS OF ESSENTIAL AMINO ACID AND CHOLINE MIXTURE (AMINOVIT) SUPLEMENTATION IN TRADITIONAL FEED ON MALE BALI PIGS PERFORMANCE - SUMADI I K.; I P. ARI ASTAWA; A. A. P. P. WIBAWA; A. W. PUGER (Majalah Ilmiah Peternakan, 2018)
This study was conducted to know the right amount of amino acid and choline (Aminovit) mixture in traditionalfeeds on male bali pigs for 12 weeks. The design used was a completely randomized design (CRD) with fourtreatments and each treatment consisted of 4 replications, so 16 male bali pigs using with a weight range of 11.60-14.10 kg. The feed treatment were P0 treatment: mixed base feed of 49.5% yellow maize and 49.5% pollard; P1:treatment P0 + 0,50% Aminovit; P2: P0 + 1.00% Aminovit; and P3: treatment P0 + 1.5 Aminovit. The performancemeasured were initial body weight, final body weight, body weight gain, feed intake, and feed conversion ratio(FCR). The results showed that increasing Aminovite in the feed increased of final body weight, body weight gainand feed consumption, and feed efficiency.